คุณภาพชีวิตการทำงานของอาจารย์พยาบาลในสถาบันสมทบ มหาวิทยาลัยมหิดล - บุญรอด, วัลลภา; ศุจิจันทรรัตน์, รัชนี; ทองเจริญ, วิไลวรรณ; คำแสน, ณัฏฐวรรณ; เทอร์เนอร์, กมลรัตน์; กรีทอง, พวงผกา; อ่วมพราหมณ์, กนกภรณ์; เชยสุวรรณ, วัชราพร; สระทอง, ผุสดี; ทิพย์เที่ยงแท้, ชิตสุภางค์; คันธา, อรุณรัตน์; เปาโรหิตย์, วัชราภรณ์; et al. (Journal of The Royal Thai Army Nurses, 2013)
-